Swearing in of 1989 Fresno County Women Lawyers Officers and Board Members - Watkins, Howard::::::::: (1998)
California Women Lawyers District 5 Governor Doris Coleman swearing in L to r: Vice President Dianna Codde, At-Large Rep. Jane Olmos, Secretary Susan Anderson, President Ruth Ratzlaff, Treasurer Jeannette Nishimori